Study of The Effect of Coconut Shell Mixture As a Substitutional Material for Coarse Aggregate on The Compressive Strength of Concrete F'c 20 Mpa (Coconut Shell Ex. Pasar Kemakmuran) - Heldita, Dina (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2023)
Coconut shell is a hard layer made up of lignin and cellulose which has a low water content, the hard structure of coconut shell is caused by silicate (SiO2) which is quite high, silicate itself is known to increase the compressive strength of concrete, the shape of coconut shell has a hard layer and a rough surface texture so that the bond with cement paste will be stronger. Therefore, if coconut shell can be technically proven as a material or aggregate for concrete mixes, it is expected to reduce the impact of environmental pollution. In this research, coconut shells were crushed into pieces with a maximum size of 20 mm x 20 mm and used as a substitute for coarse aggregate mixed with fine aggregate, water and type 1 cement. The percentages of coconut shell used in this study were 0%, 2.5% and 5%. Moulded in the form of a cylinder measuring 15x30 cm. The aim of this study is to analyze the characteristics of f'c 20 MPa concrete with the addition of coconut husk and to obtain effective mix variation through compressive strength tests at 14 and 28 days. From the research results, it can be shown that the compressive strength of normal concrete at the age of 14 and 28 days is 22.081 Mpa, 18.684 Mpa, 20.948 Mpa, 20.099 Mpa, 19.816 Mpa, 24.912 Mpa, 23.213 Mpa, 21.515 Mpa, 20.099 Mpa and 21.231 Mpa respectively. The compressive strength of concrete with 2.5% of coconut shell at 14 and 28 days is 20.948 Mpa, 19.816 Mpa, 16.985 Mpa, 20.948 Mpa, 19.816 Mpa and 16.985 Mpa, respectively. The compressive strength of concrete with 5% of coconut shell at 14 and 28 days is 18.117 Mpa, 16.419 Mpa, 14.154 Mpa, 18.684 Mpa, 18.117 Mpa, 17.551 Mpa, respectively. Thus, the compressive strength of concrete with 2.5% and 5% coconut shell substitution can reduce the compressive strength of concrete from the targeted compressive strength.